2015
DOI: 10.7763/joebm.2015.v3.303
|View full text |Cite
|
Sign up to set email alerts
|

Performance Direction towards Performance Achievement: Case on Local Islamic Banks in Malaysia

Abstract: Performance of a company is important for identifying its survival ranking and for its future direction, improvement and development strategy. Bank performance has conventionally been measured using financial ratios and several quantitative indicators, which appraise its financial strength. The same yardstick is being used by Islamic banks to measure their performance. This practice gives rise to the question whether Islamic banks appear to be focusing on Maqasid al-Shari'ah in their achievements or they share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Basah and Yusuf (2013) link the concept of Islamic CSR to the Islamic principles of Maqasid-Al-Shariah and maslahah, which may sometimes involve the same meaning (Dusuki and Abdullah, 2007a). Maslahah implies public good or public benefit, whereas Maqasid constitutes the main goal of the Shariah , which is to promote well-being and human development through education, the eradication of poverty (Sairally, 2007) and justice establishment (Amin et al , 2015; Antonio et al , 2012; Shamsudin and Mohammed, 2015). Thus, Islamic banks, as any other Islamic institution, have a sense of social responsibility (Farook, 2007), being urged to respect Maqasid, which may serve as an adequate guide for Islamic CSR (Dusuki and Abdullah, 2007a; Yusuf, 2012).…”
Section: The Concept Of Csr In Islamic and Conventional Banksmentioning
confidence: 99%
“…Basah and Yusuf (2013) link the concept of Islamic CSR to the Islamic principles of Maqasid-Al-Shariah and maslahah, which may sometimes involve the same meaning (Dusuki and Abdullah, 2007a). Maslahah implies public good or public benefit, whereas Maqasid constitutes the main goal of the Shariah , which is to promote well-being and human development through education, the eradication of poverty (Sairally, 2007) and justice establishment (Amin et al , 2015; Antonio et al , 2012; Shamsudin and Mohammed, 2015). Thus, Islamic banks, as any other Islamic institution, have a sense of social responsibility (Farook, 2007), being urged to respect Maqasid, which may serve as an adequate guide for Islamic CSR (Dusuki and Abdullah, 2007a; Yusuf, 2012).…”
Section: The Concept Of Csr In Islamic and Conventional Banksmentioning
confidence: 99%
“…In the context of the AAOIFIs, studies have shown that a stable Islamic financial environment leads to the achievement of the objective of sustainable development and an improvement in economic growth (Hassan et al, 2019). Islamic accounting standards must also respect several societal values and environmental requirements (Shahwan & Hasan, 2013;Shamsudin & Mohammed, 2015). For this, the adoption of these standards generates economic development and social progress (Asutay, 2008).…”
Section: Economic Growthmentioning
confidence: 99%